Exploring gender differences in retirement preparedness behaviours in Canada: a health belief model approach to understanding perceived motivators, barriers and behavioural moderators - Staples, Tanya M. (My University, 2025)
Women increasingly play a pivotal role in personal wealth in Canada, controlling more than $2 trillion in financial assets; a value projected to double within the next five years. Unfortunately, Canadian women are plagued by unique financial challenges such as lower earnings levels, disrupted career patterns, investment risk aversion, lower financial knowledge, increased longevity and increased incidents of financial insecurity. Using the health belief model this study explores the motivators driving retirement preparedness behaviours of women, focusing on perceived barriers, benefits and threats. Using the 2019 Canadian Financial Capabilities Study (CFCS) this dissertation employs a quantitative approach using a one-paper, four model framework. Statistical methods include path and regression analysis as well as moderation testing. By identifying gender-specific barriers and motivators that influence retirement preparedness behaviours, actionable recommendations can be developed for practitioners and policymakers to improve retirement outcomes for all Canadians, particularly women. Additionally, this dissertation contributes to the literature on financial knowledge, behavioural psychology, and gender-specific financial and retirement planning strategies.
Keywords: Retirement preparedness; Health belief model; Perceived barriers; Perceived benefits; Perceived threats; Objective financial knowledge